2020 Breastfeeding Report Card: We Must Do More!. Issue 1 (January 2021) - Spatz, Diane L.
Abstract : The 2020 Breastfeeding Report Card by the Centers Disease Control and Prevention was released in August 2020 in time for World Breastfeeding Week and National Breastfeeding Month. Our breastfeeding expert, Dr. Spatz, explains the findings and makes recommendations about what nurses can do to promote breastfeeding.